2017
DOI: 10.1002/anie.201612647
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Renal‐Clearable Gold Nanoparticles with Tumor Microenvironments: Vasculature and Acidity Effects

Abstract: The success of nanomedicines in the clinic depends on our comprehensive understanding of nano–bio interactions in tumor microenvironments, which are characterized by dense leaky microvasculature and acidic extracellular pH (pHe) values. Herein, we investigated the accumulation of ultrasmall renal-clearable gold NPs (AuNPs) with and without acidity targeting in xenograft mouse models of two prostate cancer types, PC-3 and LNCaP, with distinct microenvironments. Our results show that both sets of AuNPs could eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 55 publications
(43 reference statements)
0
37
1
Order By: Relevance
“…The reason is that PEG‐AuNPs had three‐fold larger AUC than GS‐AuNPs (142.8 %ID h g −1 vs. 47.2 %ID h g −1 , 0–24 h p.i.). GC‐AuNPs targeted PC‐3 (human prostate cancer) xenograft tumors at an efficiency of 4.36 % ID g −1 , which was about two‐fold higher than that of GS‐AuNPs (2.72 %ID g −1 ), owing to larger AUC (201.6 vs. 47.5 %ID h g −1 ) . More interestingly, for sub‐nanometer gold nanoclusters, a linear relationship was found between the AUC and the tumor‐targeting efficiency in xenograft MCF‐7 model: with an increase in AUC from 49.31 to 141.55, 201.81, and 247.58 %ID h g −1 , the 24‐h tumor accumulation linearly increased from 2.28 to 4.89, 6.07, and 8.17 %ID g −1 for Au 25 , Au 18 , Au 15 , and Au 10‐11 , respectively (Figure D) .…”
Section: Interactions With Tissues and Organsmentioning
confidence: 96%
See 3 more Smart Citations
“…The reason is that PEG‐AuNPs had three‐fold larger AUC than GS‐AuNPs (142.8 %ID h g −1 vs. 47.2 %ID h g −1 , 0–24 h p.i.). GC‐AuNPs targeted PC‐3 (human prostate cancer) xenograft tumors at an efficiency of 4.36 % ID g −1 , which was about two‐fold higher than that of GS‐AuNPs (2.72 %ID g −1 ), owing to larger AUC (201.6 vs. 47.5 %ID h g −1 ) . More interestingly, for sub‐nanometer gold nanoclusters, a linear relationship was found between the AUC and the tumor‐targeting efficiency in xenograft MCF‐7 model: with an increase in AUC from 49.31 to 141.55, 201.81, and 247.58 %ID h g −1 , the 24‐h tumor accumulation linearly increased from 2.28 to 4.89, 6.07, and 8.17 %ID g −1 for Au 25 , Au 18 , Au 15 , and Au 10‐11 , respectively (Figure D) .…”
Section: Interactions With Tissues and Organsmentioning
confidence: 96%
“…In 2013, through a comprehensive comparison of the passive tumor targeting of renal‐clearable NIR‐emitting GS‐AuNPs and a renal clearable organic dye, IRDye 800CW, we found that the EPR effect can still be retained in renal clearable GS‐AuNPs, which exhibited a much longer tumor retention time and faster normal tissue clearance than IRDye 800CW . Through the EPR effect, renal clearable GS‐AuNPs can target different types of cancers, including breast, prostate, and brain cancers (Figure and Table S8).…”
Section: Interactions With Tissues and Organsmentioning
confidence: 98%
See 2 more Smart Citations
“…To understand the surface-charge effect on renal clearance and PK of AuNPs,w ec ompared two same-sized, negatively charged zwitterionic AuNPs,GS-AuNPs (core size of 2.1 nm, zeta potential of À48.0 mV at pH 7.4) [40,57] and glutathione/cysteamine-coated AuNPs (GC-AuNPs,core size of 2.3 nm, zeta potential of À22.1 mV at pH 7.4). At 1hpostintravenous injection, liver uptake of the two types of NPs was less than 7%ID g À1 but GC-AuNPs showed much lower renal clearance efficiency (10 %ID) than GS-AuNPs (28 %ID), indicating that the renal clearance was slowed down with decreasing zeta potential in the negative charge range.PKs tudies suggested that GC-AuNPs and GS-AuNPs had comparable V d values (2.81 vs.2 .98 mL;T able S6).…”
Section: Surface-charge Effectmentioning
confidence: 99%